1972
DOI: 10.2307/2406982
|View full text |Cite
|
Sign up to set email alerts
|

The Breakdown of Trimorphic Incompatibility in Oxalis Section Corniculatae

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Society for the Study of Evolution is collaborating with JSTOR to digitize, preserve and extend access to Evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
84
1
2

Year Published

1976
1976
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 10 publications
0
84
1
2
Order By: Relevance
“…The only major difference between inheritance of tristyly in section Laxae and section lonoxalis is the complication of polysomic inheritance in some species of section lonoxalis. The genetic system controlling expression of style forms in tristylous taxa of Oxalis section Corniculatae is also similar to the system found in section lonoxalis, although there is no evidence for linkage (Ornduff, 1972). As a result of the self-compatibility which is common in section Corniculatae, homozygous short genotypes are occasionally encountered.…”
Section: Discussiomentioning
confidence: 66%
See 1 more Smart Citation
“…The only major difference between inheritance of tristyly in section Laxae and section lonoxalis is the complication of polysomic inheritance in some species of section lonoxalis. The genetic system controlling expression of style forms in tristylous taxa of Oxalis section Corniculatae is also similar to the system found in section lonoxalis, although there is no evidence for linkage (Ornduff, 1972). As a result of the self-compatibility which is common in section Corniculatae, homozygous short genotypes are occasionally encountered.…”
Section: Discussiomentioning
confidence: 66%
“…As a result of the self-compatibility which is common in section Corniculatae, homozygous short genotypes are occasionally encountered. Self-pollinations revealed that a short-mid-long sequence of dominance is also found in section Corniculatae (Ornduff, 1972). More significant differences are found in the control of tristyly in Oxalis rosea, where von Ubisch (1926) demonstrated that the short allele was recessive.…”
Section: Discussiomentioning
confidence: 98%
“…What is perhaps more remarkable is the stability of floral trimorphism in the face of these ecological pressures. This is in contrast to several self-compatible tristylous taxa in which extensive genetic modifications to the sexual polymorphism have been documented in association with colonization of marginal or disturbed environments (Ornduff 1972;Barrett 1979;Barrett et al 1989;Eckert and Barrett 1994). It seems likely that the maintenance of a strong trimorphic incompatibility system in L. salicaria serves to buffer the mating system against inbreeding and consequent opportunities for the spread of recessive mutations modifying the sexual polymorphism (Charlesworth 1992;Fenster and Barrett 1994).…”
Section: Morph-frequency Variation In Native Versus Introduced Populamentioning
confidence: 73%
“…and Phillyrea angustifolia [Oleaceae] [Lepart and Dommée, 1992;Yamazaki, 1993;Hiura and Ishida, 1994;Ishida and Hiura, 1998;Dommée et al, 1999] [Ornduff, 1964[Ornduff, , 1972, Saxifraga cernua [Saxifragaceae] [Molau and Prentice, 1992], and Schizopepon bryoniaefolius [Cucurbitaceae] [Akimoto, Fukuhara, and Kikuzawa, 1999]). A few plant species show ''monoecious'' cosexes with pistillate and staminate flowers on the same inflorescences (Ricinocarpos pinifolius and Mercurialis annua [Euphorbiaceae] [Thomson et al, 1989;Pannell, 1997], and Sagittaria lancifolia [Alismataceae] [Muenchow, 1998] (Fig.…”
mentioning
confidence: 99%